2012
DOI: 10.5213/inj.2012.16.1.37
|View full text |Cite
|
Sign up to set email alerts
|

The Relations between Enuresis in Childhood and Nocturnal Polyuria Syndrome in Adult Life

Abstract: PurposeThe aim of this study, to investigate whether there is any association between enuresis in childhood and nocturnal polyuria syndrome (NPS) in adult life.MethodsThe study consisted of thirty five patients with nocturnal polyuria, and thirty five healthy people without nocturnal polyuria in adult life, were asked to assess their enuresis in childhood.ResultsThere was a history of enuresis in childhood in 18 (51.42%) of 35 of men with nocturnal polyuria and in 4 (11.42%) of 35 without nocturnal polyuria. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
(26 reference statements)
0
6
1
Order By: Relevance
“…A genetic inheritance of SNE with associated DO has also been proposed . Current evidence is conflicting on the role of reduced bladder capacity in the pathophysiology of nocturnal enuresis . The mean maximum cystometric capacity was slightly lower in women with SNE in our study (mean difference of 53.3, P < 0.001), which does indicate a lower bladder capacity as a possible factor in the pathogenesis of NE.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…A genetic inheritance of SNE with associated DO has also been proposed . Current evidence is conflicting on the role of reduced bladder capacity in the pathophysiology of nocturnal enuresis . The mean maximum cystometric capacity was slightly lower in women with SNE in our study (mean difference of 53.3, P < 0.001), which does indicate a lower bladder capacity as a possible factor in the pathogenesis of NE.…”
Section: Discussioncontrasting
confidence: 93%
“…20 Current evidence is conflicting on the role of reduced bladder capacity in the pathophysiology of nocturnal enuresis. 16,21,22 The mean maximum cystometric capacity was slightly lower in women with SNE in our study (mean difference of 53.3, P < 0.001), which does indicate a lower bladder capacity as a possible factor in the pathogenesis of NE. A low MUCP was an independent risk factor associated with SNE and was significantly low in the study group, also suggesting a possible role in the etiopathogenesis of SNE.…”
Section: Discussionmentioning
confidence: 42%
“…Moreover, a history of enuresis in childhood seems to increase the risk of having nocturnal polyuria syndrome in adult life. Therefore, enuresis in children requires aggressive treatment …”
Section: Discussionmentioning
confidence: 61%
“…Therefore, enuresis in children requires aggressive treatment. 2,12,13 We found that 9.3% of children with SDB had NE, and that the prevalence of NE was significantly higher in the severe SDB (OSA) group comprising children with a SDB scale 8 than the mild SDB group (13.1% vs. 3.9%). Because a wide range of prevalence rates of NE has been calculated using different cutoff values to define SDB and NE, a simple comparison of our results with those of previous studies is unlikely to be accurate.…”
Section: Discussionmentioning
confidence: 90%
“…Since approximately the year 2000, surveys in adults with LUTS have shown that NE and childhood daytime urinary incontinence are associated with an overactive bladder . They have also shown that childhood nocturia and NE are associated with nocturia and urgency and that NE is associated with nocturia , urinary incontinence and nocturnal polyuria . However, because these surveys only targeted adult women, or included a small number of adults, a number of potentially associated factors remain unexplored, including NE severity, sex and the age when childhood NE was resolved.…”
Section: Discussionmentioning
confidence: 99%